High level referees' decisions making - David Molero López-Barajas (FEADEF, 2011)
We show, in this work, a study based on the analysis of handball referees' decisions making from the marks got in the spanish adaptation of Decision Making Questionnaire dealing with the following factors: stress in making decisions, quick decision with uncertainty and determination in the commitment of decisions making. We found significant differences in the three factors considered in function of the category of referees but not in terms of their age. With the data are collected and analyzed future lines of action considered in which the basis for this group tutoring